(untitled) (Research, Society and Development, 2020)
This article aims to analyze the degree of Sustainable Development of the city of Parauapebas, located in the state of Pará in a region of great importance in the context of mineral exploration in the Amazon. In this scenario, urban sustainability analysis are difficult to conduct, making it difficult to implement public policies oriented to sustainable development in the city. Given this problem, a quantitative analysis was carried out by calculating the Municipal Sustainable Development Index (IDSM) of the three dimensions that constitute the Triple Bottom Line approach: Social, Economic and Environmental. Thus, a comparative calculation methodology was used involving variables collected in official government bases that represent the scenarios at municipal and state levels, allowing a comparison of regional realities with the studied city. The results showed an average IDSM value of 0.71, a measure classified as acceptable. Finally, the efficiency of the methodology used was analyzed regarding the realistic social, economic and environmental scenarios found in the municipality that has one of the largest mineral wealth in Latin America.